Concept Images of pre-service mathematics teachers in educational and science faculties regarding the basic concepts of geometry - (:unkn) unknown (Sakarya University, 2015)
The main purpose of this research is to determine the concept images of pre-service mathematics teachers in educational and science faculties regarding the basic concepts of geometry (line, line segment, plane, space, vectors and vector operations). The study group of the research was consisted of 90 pre-service teachers majoring in mathematics in a public university educational and science faculties. The Geometrical Concept Test about particular mathematical concepts including four open-ended questions was applied to pre-service teachers. The data of this study were evaluated by using qualitative and quantitative research methods. Quantitative data was obtained through frequency and percentages and qualitative data was collected by coding the responses provided by the pre-service teachers to the open-ended questions. An agreement over the data was reached by comparing the data which was coded independently by the researchers with each other. After deciding on the common evaluation criteria, concept images of the pre-service teachers regarding the basic geometrical concepts were analyzed. According to the findings obtained in this study, pre-service teachers both in educational and science faculties had inadequate concept images regarding the basic geometrical concepts according to their grade levels including freshman students with the lowest rates. Pre-service teachers reported that they did not recognize the importance of the concepts as they did not investigate the definitions of the concepts and the importance of this case was not emphasized. Suggestions were made for the future researchers in the light of the research findings. © The Turkish Online Journal of Educational Technology.
Keywords: Mathematics teachers